Lean Maintenance Approach Optimization of Apartment Building Maintenance Based on Cost Performance - Girsang, Hamonangan; Irvan Suwandi Hasan; Yopi Lutfiansyah; Elhazri Hasdian; Ernanda Dharmapribadi (Rekayasa Sipil, 2026)
Based on the building maintenance report for the fiscal year 2022-2023 as received by the owner of a nine-story apartment building located in Indonesia, building repairs, maintenance, and similar activities were carried out and required due to several building components requiring repairs, such as roof leaks, water-stained ceilings, garden repairs, lighting, and so on, with a total repair cost of IDR 67,938,538.48 in the civil works, exceeding the planned annual budget. This aligns with customer feedback (VOC), which indicates that traditional maintenance methods may be less accurate at predicting the annual maintenance budget for a building. However, as building complexity increases, traditional maintenance management methods are no longer recommended. The importance of efficiency in the maintenance system has been demonstrated by a recent study that seeks to link lean principles to maintenance strategies. In this study, an evaluation of the maintenance system will be carried out using qualitative and quantitative methods based on the lean maintenance principles approach. From the results of the assessment carried out, the company gave high scores for all lean maintenance principles, namely identify the value (10/10), map the value stream (7.5/10), continuous flow (7.25/10), establish pull (7.75/10), and seek perfection (10/10). The system improvements needed are creating a value flow map (VSM) and implementing an ERP (Enterprise Resource Planning)-based material inventory for the management, monitoring, and processing of material information. The value-added ratio under the lean method increased from 14.67% to 77%, and maintenance costs were 51% lower.